(untitled) (Annals of Medical Research, 2023)
Aim: Obesity is a global health burden with an increasing worldwide incidence. Coronary artery ectasia (CAE) is frequently associated with obstructive coronary artery disease and acute coronary syndrome (ACS). Obesity and CAE are risk factors for ACS. Considering this linkage, we aimed to investigate the role of obesity in presence of CAE in patients presenting with ACS. Materials and Methods: Patients hospitalized with a diagnosis of ACS in our tertiary center between January 2015 and May 2020 were included in this retrospective, case-control study. The patients presenting with ACS involving a coronary artery ectasia segment formed ‘CAE group’. On the other hand, patients who were undergone coronary angiography with a diagnosis of ACS without coronary ectasia formed ‘control group’. Results: There were a total of 274 patients. Patients who were presented with ACS involving a CAE segment were in higher body mass index (BMI) tertials and BMI was an independent predictor for presence of CAE in patients presenting with ACS. Additionally advanced age, diabetes mellitus, hypertension, current smoking, increased neutrophil/lymphocyte ratio, higher fasting blood glucose, triglyceride and lower high-density lipoprotein (HDL) levels were found as independent risk factors for presence of CAE in patients presenting with ACS. Conclusion: We detected obesity (being overweight or obese) as an independent risk factor associated with the presence of CAE in patients presenting with ACS. Higher triglyceride and fasting blood glucose and lower HDL levels detected in our study support the idea that metabolic syndrome plays a role and insulin resistance is the underlying mechanism for CAE presence in patients presenting with ACS.